Role of salivary immunoglobulins in oral health: Investigating levels of IgA and IgG in saliva and their impact on periodontal disease among patients in Peshawar, Pakistan - Muhammad Abdullah Zuhair (Annales Academiae Medicae Silesiensis)
Introduction: Salivary immunoglobulins, IgA and IgG, play a crucial role in the oral immune system, influencing oral health. Given the high prevalence of periodontal disease in Pakistan and the influence of socio-cultural factors on oral health practices, this study aims to assess the levels of salivary immunoglobulins to periodontal health. Material and methods: A cross-sectional study was conducted involving 99 participants aged 18 to 65, grouped by periodontal health and smoking status: healthy non-smokers, smokers with gingivitis, and smokers with periodontitis. Patients having other comorbidities such as diabetes mellitus, cardiovascular diseases, neurological diseases and severe periodontitis were excluded. The participants were recruited from dental clinics in Peshawar. Salivary samples were collected, and immunoglobulin levels were measured using an enzyme-linked immunosorbent assay (ELISA). Clinical parameters, including bleeding on probing (BOP), the probing pocket depth (PPD), and plaque index (PI), were also recorded. Statistical analysis was performed using SPSS version 25, with the Pearson correlation coefficient to assess relationships between the immunoglobulin levels and clinical parameters. Results: The study found that salivary immunoglobulins levels were significantly higher in the groups of participants being smokers (66%) having gingivitis (IgA: 1.5 mg/mL, IgG: 1.1 mg/mL) and periodontitis (IgA: 2.5 mg/mL, IgG: 2.0 mg/mL) compared to healthy non-smoking (33%) individuals (IgA: 0.4 mg/mL, IgG: 0.3 mg/mL). Additionally, the BOP and PPD values were the lowest in the healthy non-smoking participants and increased significantly in the smoking group with periodontal disease. Conclusions: Elevated levels of salivary immunoglobulins correlate with periodontal disease and smoking, indicating their potential as biomarkers for diagnosis and monitoring treatment.